Prognostic significance of the preoperative lactate dehydrogenase-to-albumin ratio in patients undergoing radical resection for hilar cholangiocarcinoma - Li, Guoan; He, Tao; Geng, Mingyue; Qi, Fuzhen (Frontiers in Medicine, 2025)
BackgroundHilar cholangiocarcinoma (HCCA) is an aggressive malignancy with a poor prognosis even after curative resection. Accurate prognostic assessment is crucial for individualized treatment and postoperative management. The lactate dehydrogenase-to-albumin ratio (LAR), a composite marker that reflects both tumor metabolism and the host’s nutritional-inflammatory status, has demonstrated prognostic value in several cancers. However, its role in HCCA remains unclear.MethodsWe retrospectively analyzed 112 patients who underwent radical resection for HCCA between 2017 and 2022. Preoperative LAR was calculated from routine laboratory tests. Optimal cut-off values for LAR, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were determined using maximally selected rank statistics. Clinicopathological characteristics were compared between LAR groups. Prognostic factors for overall survival (OS) were evaluated using univariate and multivariate Cox regression analyses. Subgroup analyses assessed the consistency of LAR effects across clinical strata.ResultsThe optimal LAR cut-off was 4.67. Patients with high LAR (>4.67) were older and had higher rates of hypertension, lymph node metastasis, and elevated bilirubin, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels. In univariate analysis, high LAR, PLR, NLR, carbohydrate antigen 19-9 (CA19-9), total bilirubin (TBIL), ALT, AST, lymph node metastasis, poor differentiation, and R1 resection were significantly associated with worse OS. Multivariate analysis identified high LAR [hazard ratio (HR) 1.70, confidence interval (CI) 1.01–2.87, p = 0.046], high PLR (HR 2.12, 95% CI 1.26–3.55, p = 0.004), ALT ≥50 U/L (HR 2.94, 95% CI 1.27–6.77, p = 0.012), poor differentiation (HR 0.51, 95% CI 0.33–0.83, p = 0.006), and microscopically incomplete resection (R1 resection) (HR 2.04, 95% CI 1.14–3.64, p = 0.012) as independent predictors. Subgroup analyses showed a consistent adverse effect of high LAR across most strata without significant interactions.ConclusionPreoperative LAR is an independent prognostic biomarker for patients with HCCA undergoing radical resection. As a simple, cost-effective, and routinely available index, LAR may assist in risk stratification and postoperative management. External validation is warranted to confirm its clinical utility.